ANALISIS HKRITIS TERHADAP DAYA DUKUNG TANAH DASAR - Lutfi D. Nasution; Munirwansyah Munirwansyah; Sofyan M. Saleh (Prodi Magister Teknik Sipil Unsyiah, 2018)
The addition of the existing heap on the ground interface will affect the ability of subgrade to accept the burden of the embankment and other charges on it. The inability of subgrade in accepting the load will result in a decrease in the vertical deformation and collapse. The analysis was conducted on the National Roads Banda Aceh-Medan KM. 83 + 135 of the Seulawah. The purpose of this study is to analyze whether the brunt of the height of the pile (H Critical) have exceeded the carrying capacity of the subgrade. The analysis was performed by using Plaxis software. The implementation method used in the analysis based on the modeling of the pile height variations by reducing the height of the pile with a certain interval gradually until a critical height (H Critical) heap that causes the achievement of maximum decrease of 2.5 cm. The modeling result demonstrates that when the consolidation of the soil embankment on condition of Hheap soil = 6 m, Hheap soil= 5.4 m, Hheap soil = 4.8 m could able to reduce the height of the soil embankment by 10%, 20%, and 30%, and considered in an unsafe condition. While when the soil embankment consolidation reduce by 40% (H heap soil = 3.6 m) showing in a safe condition. This result shows that the forces acting on the pile-soil could not hold the load so that the interface is about to collapse.